Kauṭalīyaṃ : bhāṣāvyākhyānasahitaṃ - Kauṭalya (Pṟasiddhīkaraṇavakuppȧ, Kēraḷasarvvakalāśāla, 1972)
Old Malayalam translation of Cāṇakyā's Arthaśāstra, ancient Sanskrit work on administration and political science; includes commentary and text in Malayalam script.